DETERMINAN PINJAMAN PEMERINTAH DAERAH PROVINSI DI INDONESIA - Yulsiati, Henny; Maqruf, Romibil (Balance : Jurnal Akuntansi dan Bisnis, 2022)
This examination expects to inspect the impact of nearby credit on the commonplace government. The example utilized in this examination was acquired utilizing the purposive testing strategy, so an example of 8 Commonplace Governments in Indonesia in 2015-2019 was gotten. The information utilized in this examination is auxiliary information. The investigation procedure utilized is numerous straight relapse examination. Information testing was done utilizing Eviews variant 10 programming. The aftereffects of the t-test showed that nearby income and general assignment supports had no impact on neighborhood credit. Capital Use has a positive and critical impact on territorial credit in the territories in Indonesia. The consequences of the F test show that the factors of territorial unique pay, general assignment assets, and capital consumptions together affect provincial credit in territories in Indonesia.